Real-world effectiveness of voxelotor for treating sickle cell disease in the US: a large claims data analysis. Issue 2 (1st February 2022) - Shah, Nirmish; Lipato, Thokozeni; Alvarez, Ofelia; Delea, Thomas; Lonshteyn, Alexander; Weycker, Derek; Nguyen, Andy; Beaubrun, Anne; Agodoa, Irene
ABSTRACT: Background: Sickle cell disease (SCD) is a genetic disease that impacts patients' quality of life, healthcare costs, and life expectancy. Elevated sickle hemoglobin (HbS), which readily polymerizes, causes red blood cell sickling, leading to chronic hemolytic anemia and complications often requiring hospitalization and transfusions. In 2019, voxelotor, which inhibits HbS polymerization, was approved for SCD treatment. Objectives: This study uses real-world evidence to assess voxelotor's effectiveness in SCD patients in typical clinical practice from 2019 to 2021 using a national medical claims database (N = 3128). Results: After initiating voxelotor, 60.8% of patients with available hemoglobin (Hb) laboratory data (n = 74) showed a Hb increase >1 g/dL. Mean transfusion rate per patient-year dropped 52% in patients with ≥1 transfusion before treatment (n = 190). In patients with ≥1 of the corresponding events (n = 1065), decreases were observed in mean vaso-occlusive crisis (VOC) frequency (–23%); mean VOC-related hospitalizations and length of stay (LOS) time (–34% and –30%, respectively); mean all-cause hospitalization and LOS time (–37% and –23%, respectively); outpatient visits (–10%); iron chelation use (–46%); and prescribed opioids (–13%). Conclusion: These data align with randomized controlled trial results showing voxelotor improvements and support that voxelotor may lower transfusion and VOC rates in clinical practice.